Enquete - Andersen, Iben Engelhardt; Flohr, Mikkel; Frantzen, Mikkel Krause; Gade, Solveig; Haarder, Jon Helt; Helland, Frode; Juhl, Carsten; Ladegaard, Jakob; Lund, Jacob; Nielsen, Henrik Kaare; m.fl. (K&K - Kultur og Klasse, 2016)
Kritik i dag